Development of Worksheet Based on Search Solve Create and Share (SSCS) on Learning Interest, Science Process Skills and Student Learning Outcomes in Biology Material of First Level (X Class) Senior High School - Josephine Olivia Gultom; Idramsa Idramsa; Fauziyah Harahap (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
This study develops and tests (LKPD) based on search, solve, create, and share (SSCS) in biology learning for class X MIA Semester I at SMA Negeri 5 Medan. To actively assess students' learning interests, science process skills, and learning outcomes at school because this process helps students search, find, and build their knowledge to solve problems. This research is development. Uses 4D development research (Define, Design, Develop, Disseminate). Interviews, material expert validation questionnaires, design validation questionnaires, language validation questionnaires, study field teacher responses to SSCS-based LKPD, student learning interest questionnaires, student science process skills questionnaires, and pretest-posttest assessment sheets were used. Material experts rate material validity as "Very Good/Decent" with an average of 91.75%. Design expert product quality results averaged 87.5% "Good/Decent". Teacher responses on the SSCS-based LKPD averaged 86.25% "Good/Decent". Students are 71% "Interested" in learning in small groups and 88% "Very Interested" in large groups. Science students' process skills averaged 86.67 in the big group and 76.67 in the small group in the "Good/Decent" category. Out of 37 students, 4 had a "Medium" N-gain of 0.7 on the biodiversity and virus meters, whereas 33 had a "High" N-gain of 0.8.